SALINITY AGRICULTURAL PROBLEM IN AGRICULTURAL LANDS - Fattah, Mahdi Fahmi; Nawkhas, Burhan Nareeman (Journal of Medical Genetics and Clinical Biology, 2026)
Objective: This study aims to address the increasing challenge of soil salinity as a critical barrier to sustainable agricultural production, emphasizing the essential roles of soil and water quality in maintaining productivity. Method: The research employs a descriptive and analytical approach, examining the causes of soil salinization in dry and semi-arid regions by differentiating between natural and human-induced factors, including improper irrigation practices, poor drainage, and excessive fertilizer use. Results: The findings indicate that the persistent use of low-quality irrigation water due to water scarcity and pollution accelerates salinity accumulation in agricultural soils, leading to a significant decline in soil fertility and crop yield. The study highlights that effective mitigation requires leaching techniques, improved irrigation management, and the cultivation of salt-tolerant crops. Novelty: This article provides an integrative perspective that combines ecological and agronomic factors, offering practical strategies to rehabilitate saline soils and promote sustainable agriculture, especially in regions facing increasing water stress due to climate change.